Genetics and breeding of sheep in Brazil Genética e melhoramento de ovinos no Brasil - Concepta McManus; Samuel Rezende Paiva; Ronyere Olegário de Araújo (Revista Brasileira de Zootecnia, 2010)
Studies in genetics and breeding of sheep in Brazil have increased significantly in recent years. These involve research in characterization, breeding and crossing sheep using new technologies available incorporating both classical quantitative and molecular genetics. Improvements in statistical techniques, computational resources as well as analysis of DNA and gaps in present knowledge and opportunities for possible research are pointed out. There is a need for greater interaction between various groups working in the country as well as interactions with other disciplines such as Geographical Information Systems, Statistics, Bioinformatics, as well as biological studies such as physiology and proteomics. Estudos em genética e melhoramento de ovinos no Brasil têm aumentado significativamente nos últimos anos. Estes envolvem pesquisa em caracterização, criação e cruzamento de ovinos utilizando as novas tecnologias disponíveis, incorporando tanto a genética quantitativa clássica e molecular. São abordadas sugestões para melhorias nas técnicas de estatística, nos recursos computacionais, bem como na análise de DNA e nas lacunas no conhecimento atual e possibilidades de possíveis investigações. Há uma necessidade de maior interação entre vários grupos de trabalho no país, bem como as interações com outras disciplinas, como Sistemas de Informação Geográfica, Estatística, Bioinformática, bem como estudos biológicos, como fisiologia e proteômica.